2021
DOI: 10.1088/1742-6596/1731/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive process of students understanding quadratic equations

Abstract: Algebra is mandatory learning in junior high school. That is a continuation of arithmetic with the bridge being variable. Students often have difficulty in understanding it, especially quadratic equations. The purpose of this study is how students’ cognitive processes in understanding the principles of quadratic equations. It was an exploratory study conducted on research subjects. The subjects were junior high school students selected based on their ability to understand concepts and principles about quadrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In this research, algebraic manipulations and visual representations denote the essential connection between symbolic mathematical operations and graphical depictions within quadratic inequalities. In quadratic functions, algebraic manipulations involve the mathematical processes and transformations applied to equations, such as factoring, completing the square, or manipulating coefficients (Herawaty et al, 2021;Hoan et al, 2022;Weiss, 2016). On the other hand, visual representations pertain to the graphical depiction of these equations, particularly the parabolic graphs associated with quadratic inequalities.…”
Section: Infinitymentioning
confidence: 99%
“…In this research, algebraic manipulations and visual representations denote the essential connection between symbolic mathematical operations and graphical depictions within quadratic inequalities. In quadratic functions, algebraic manipulations involve the mathematical processes and transformations applied to equations, such as factoring, completing the square, or manipulating coefficients (Herawaty et al, 2021;Hoan et al, 2022;Weiss, 2016). On the other hand, visual representations pertain to the graphical depiction of these equations, particularly the parabolic graphs associated with quadratic inequalities.…”
Section: Infinitymentioning
confidence: 99%
“…Among the contributing factor to such weakness is that students find it difficult to give meaning or understand the terms used to represent the roots of the quadratic equations (Thomas & Mahmud, 2021). They also often make mistakes when solving quadratic equations, especially in the process of conducting operations to reach the solutions and finding the possible values for substitute variables along with the lack of understanding about fractions, integers, linear equations, negative numbers, and basic mathematical properties such as algebraic expansion (Herawaty et al, 2021). The study by Vaiyavutjamai et al (2005) also reported that many students do not know that quadratic equations have more than one root.…”
Section: Number Theorymentioning
confidence: 99%